CONSUMER ATTITUDES AND PREFERENCES IN THE TRANSITION TO ELECTRIC VEHICLES - Madhav K P, Mrinal; Mathew , Vineeth (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2024)
The global transition towards electric vehicles (EVs) has sparked significant interest in Kerala, a state at the forefront of India in e-mobility revolution. The study analyses consumer attitudes and preferences towards electric vehicles transition in Kerala, aiming to understand the factors influencing their willingness to transition from conventional engine vehicles. Through the surveys and interviews carried out in the study reveal that Kerala's consumers are enthusiastic about electric vehicles driven by concerns about environmental sustainability, fuel efficiency, and government incentives. However, range anxiety, high upfront costs, and charging infrastructure limitations remain significant barriers. The findings suggest that targeted interventions, such as investing in charging infrastructure, offering attractive financing options, and promoting awareness campaigns, can accelerate electric vehicles adoption in Kerala. This study contributes to the understanding of consumer behavior in the context of sustainable transportation and informs policy and marketing strategies to facilitate a smoother transition to electric vehicles in the region.